Hesitações na fala infantil: indícios da complexidade da língua - Jurado Filho, Lourenço Chacon [UNESP]; Villega, Cristyane de Camargo Sampaio (My University, 2012)
The aim of this study is to identify characteristics of hesitational functioning in speech productions of children with typical language development. The data were extracted from (individual) audio recordings of a short story structured as rimes by 26 children aged between 5-6 years old. Five judges made the identification of the points of hesitation in each recording and identified the brands in which the hesitations showed: silent pauses; repeting hesitations; interruptions; and hesitative elongations. Considering the global level of the narrative, 80.66% of the points of hesitation occurred in situations where changes were combined in: the rhythmic structure of the verses; the narrator’s position; and in verbal tenses. In addition, the internal structure of the verses in which these changes occurred was built with words of complex phonological configuration for the patterns of children’s speech. The 19,34% remaining points of hesitation occurred in more stable situations, regarding the global composition of the narrative as well as the internal structure of its verses. These verses were characterized by: the repetition of rhythmic structure; the presentation of the conflict in the narrative and its outcome; less complex phonological structured words regarding the children’s vocabulary. The non-random aspects of these points reinforce, thus, the idea that the hesitations exhibit points where the subject negotiates with the others constituents of (his) speech, once they occurred, privileged, in points where least expected language co-occurrences revealed themselves as a turbulent other to the children.

O objetivo do presente estudo é identificar características do funcionamento das hesitações na produção oral de crianças com desenvolvimento típico de linguagem. O material foi extraído de gravações (individuais) em áudio de uma narrativa estruturada como uma parlenda por 26 crianças entre 5-6 anos de idade. Cinco juízes fizeram a identificação dos pontos de hesitação em cada gravação bem como das marcas com as quais as hesitações se mostraram: pausas silenciosas; repetições hesitativas; interrupções; e alongamentos hesitativos. Considerado o plano mais global da narrativa, 80,66% dos pontos de hesitação ocorreram em situações em que se combinavam mudanças: de estruturação rítmica dos versos; de posicionamento do narrador; e de tempo e modo verbais. Complementarmente, a estrutura interna dos versos em que se deram essas mudanças era construída com palavras de configuração fonológica complexa para os padrões de fala infantil. Os 19,34% restantes de pontos de hesitação ocorreram em situações mais estáveis, tanto do ponto de vista da composição global da narrativa quanto da estrutura interna de seus versos. Esses versos caracterizavam-se por: repetição de estrutura rítmica; apresentação do conflito e do desfecho da narrativa; palavras de estrutura fonológica menos complexa para o vocabulário infantil. O aspecto não-casual, não-aleatório desses pontos reforça, portanto, a visão de que as hesitações indiciam negociações do sujeito com os outros constitutivos do (seu) discurso, já que ocorreram, privilegiadamente, em pontos nos quais co-ocorrências menos esperadas da própria língua se mostraram como um outro turbulento para as crianças.
Keywords: Hesitação; Aquisição de linguagem; Discurso